Pulp and Paper Processing - Newaz Kazi, Salim (IntechOpen, 2018)
This book gives emphasis to wood fiber raw materials, alternative sources of fibers for paper production, environmental issues, paper quality improvement and cost of paper production. Varieties of non-wood raw materials, including kenaf, rice straw, empty fruit bunches of palm trees, bamboo, bagasse, etc., are considered in this book. The process of fiber treatment also varied to meet paper quality improvement. Different organosolv processes of fiber treatment are discussed. Considering contemporary issues, one particular chapter analyzes the environmentally friendly way of processing non-wood fibers for paper production. The book also contains a chapter on the by-product raw materials of paper production and their profitable applications.